Islamic Education Learning Management Based on Religious Moderation Values - Mualimul Huda (MindSet : Jurnal Manajemen Pendidikan Islam, 2022)
Learning management is needed to optimize learning activities and achieve learning objectives. Through Islamic religious education (PAI) learning, students are directed to be able to actualize religious understanding in everyday life with a religious, multicultural, tolerant, and moderate attitude within the framework of the Indonesian nation and state. One of the efforts is to internalize the values ​​of religious moderation in Islamic religious education learning. The purpose of internalizing the values ​​of religious moderation is to increase students' understanding, practice tolerance, mutual respect, have a national commitment, and be anti-violence. This study aims to describe the management of PAI learning by internalizing the values ​​of character education based on religious moderation. This study uses a library research approach, descriptive data analysis method, collecting data, compiling, clarifying, and interpreting. The study results revealed that the internalization of religious moderation values ​​in PAI learning includes planning, implementation, control, and evaluation activities. Learning planning activities are guided by the content of the PAI curriculum at KMA 183 in 2019. Implementation activities include the application of approaches, methods, media and strategies, adaptive learning to religious moderation values, including student-centered learning approaches, problem-based learning, and contextual and cooperative learning. Learning evaluation activities are carried out by assessing cognitive, psychomotor, and affective aspects. The implication is that PAI teachers should continue to create and innovate learning by internalizing the values ​​of character education in the learning process.